Road, Tram and Aircraft Traffic Noise Annoyance Related to the Number of Noise Events and the Equivalent Sound Level - FELCYN, Jan; PTAK, Patrycja (Archives of Acoustics, 2022)
Noise mapping is based on long-term noise indicators, such as LN or LDEN. On the other hand, transportation intensity changes during a day (road traffic peak hours) or a year (more flights during holidays) and this variability is not reflected in single sound level values. We wanted to find out whether not only sound level but also the number of noise events is the factor influencing noise annoyance assessment. Ambisonic recordings of real traffic in a city were used. Road, tramway, and aircraft traffic were investigated and two factors were manipulated: the equivalent sound level value and the number of noise events. All stimuli were presented in an anechoic chamber. The results showed that sound level is always a statistically significant parameter while the number of events has an impact only for tramways and airplanes. Moreover, the difference is observed only between one or more subgroups, no matter what the sound level value was. For road traffic this relation was not found to be statistically significant. It was also shown that the existence of tramway bonus or airplane malus is linked with the number of noise events.